Pengaruh Tingkat Kemurnian Bahan Baku Alumina Terhadap Temperatur Sintering dan Karakteristik Keramik Alumina - Jarot Raharjo (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The influences of the purity of alumina to the sintered properties of alumina have been successfully investigated. Two types of alumina i.e., α-alumina PA (99% alumina) and technical alumina were used in this research. Various temperature sintering used in this research were 1250, 1350, 1450, 1550, and 1600oC. The powders were prepared by using wet milling method and ethanol used as a solution in a plenetary ball mill. The green body was pressed at 12 metric ton of pressure. The shrinkage, density, porosity, hardness and fracture toughnes of the sintered pellets were measured, and the microstructure of fractures pellets was observed by SEM. From the characterization found that the temperature sintering affected to the densification and properties of alumina, and the other hand the purity of raw materialcan affected to the temperature sintering of alumina ceramics. The optimum properties of α-alumina PA ceramics at 1600oC resulted the density 3.489 gr/cm3, the hardness 1668 VHN, and the fracture toughness 5.774 MPa m 1/2. However for the alumina technique ceramics resulted density level 3.082 gr/cm 3, the hardness 999 VHN and fracture toughness 1.545 MPa m1/2